Extended prophylaxis with nevirapine and cotrimoxazole among HIV-exposed uninfected infants is well tolerated - Aizire, Jim; Fowler, Mary Glenn; Wang, Jing; Shetty, Avinash K.; Chibanda, Lynda Stranix; Kamateeka, Moreen; Brown, Elizabeth R.; Bolton, Steve G.; Musoke, Philippa M.; Coovadia, Hoosen (AIDS (London, England), 2012)
Nevirapine and cotrimoxazole are associated with hematologic toxicities and skin-rash. Safety of their concurrent use for prophylaxis over extended periods among HIV-exposed uninfected infants has not been previously assessed.Secondary data analysis of the ‘HIV Prevention Trials Network-046 protocol’ (version 2.0), a phase-III, randomized, placebo-controlled trial that assessed efficacy and safety of nevirapine prophylaxis against breast milk transmission of HIV-1.Trial infants received 6-month study nevirapine/placebo, and standard-of-care peripartum single-dose nevirapine+/– zidovudine ‘tail’, and cotrimoxazole prophylaxis from 6 weeks through breastfeeding cessation. Adverse events were monitored using United States Division of AIDS Toxicity Tables (2004). Risk of neutropenia, anemia and skin-rash in the cotrimoxazole+nevirapine and the cotrimoxazole+placebo groups were compared using negative-binomial regression.Incidence of neutropenia and/or anemia, and skin-rash was highest during the first 6 weeks of life and declined, thereafter, regardless of study group. Time to first adverse event after 6 weeks was similar in cotrimoxazole+nevirapine and cotrimoxazole+placebo groups: hazard ratio (95% confidence interval) was 1.26 (0.96–1.66) for neutropenia and/or anemia (all grades), 1.27 (0.80–2.03) for neutropenia and/or anemia (grade ≥3) and 1.16 (0.46–2.90) for skin-rash (grade ≥2). There were no statistically significant differences in immediate (6 weeks–6 months) and long-term (6–12 months) adverse event risk among infants on cotrimoxazole+nevirapine versus cotrimoxazole+placebo.Extended nevirapine and cotrimoxazole prophylaxis through 6 months of age among HIV-exposed uninfected infants did not appear to increase the immediate or long-term risk of neutropenia, anemia or skin-rash. Concurrent use beyond 6 months, however, needs to be evaluated.
Keywords: anemia, cotrimoxazole, HIV-exposed uninfected infants, neutropenia, nevirapine, skin-rash